INTELLECTUAL CAPITAL PERFORMANCE: EVIDENCE FROM TOURISM AND HOSPITALITY INDUSTRY - Angkasaputra, Cindy Olivia; Aditya, Arya Aji; Azizah, Nur (Faculty of Economics and Business University of Mataram, 2022)
The purpose of this study was to determine the impact of intellectual capital on financial performance in Indonesia's hotel, restaurant, and tourism industries between 2018 and 2020. Annual reports from www.idx.co.id for the years 2018 until 2020 were used as secondary data. The sampling method was purposive sasmpling, while the measurement of human capital using VAIC. As a result, the multiple linear regression analysis finds that structural and human capital employed have an effect on financial performance while human capital does not. Based on the analysis result, we can conclude that tourism and hospitality businesses should determine the strategic role of strategic resources within the organization, particularly intellectual capital, during COVID-19. This is bolstered by the hotel, restaurant, and tourism industries, all of which rely heavily on intangible assets.